ANALISIS PEWARNA DAN PEMANIS BUATAN PADA SAUS CABAI BAKSO BAKAR DAN “SAUS GEJROT TAHU DANGDUT” YANG DIJAJAKAN DI KAWASAN USU TAHUN 2015 - Febri Hakiki; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Chili sauce and “saus gejrot” (spattered sauce) is a food processing product which popular among the students of USU (University of Sumatera Utara) because it is used in the students’ favorite snacks, grilled bakso (meat ball) and “tahu dangdut” (the name of a kind of tofu). Generally, the process of making the sauce added dyes and artificial sweeteners to get the maximum results with low production costs . The research was a descriptive survey in order to find out whether or not there was coloring matter in chili sauce of grilled bakso and artificial sweetener in “saus gejrot” of “tahu dangdut” sold at USU in 2015 by conducting laboratory test qualitatively and quantitatively. The unit of analysis in this study are some of the chili sauce from 5 chili sauce used on grilled meatballs and some